2022
DOI: 10.1002/jlb.3ma0322-428r
|View full text |Cite
|
Sign up to set email alerts
|

Sophoridine inhibits endotoxin-induced acute lung injury by enhancing autophagy of macrophage and reducing inflammation

Abstract: Acute lung injury (ALI) is characterized by uncontrolled inflammation, which can lead to respiratory distress syndrome and cause patient death. In this study, we sought to determine the role of sophoridine, a compound purified from sophora, in ALI. A mouse model of ALI was established by treating mice with LPS through nonexposed tracheal instillation. After LPS‐induced mice were treated with sophoridine, LPS‐induced alveolar wall thickening, alveolar interstitial inflammatory exudation and thickening, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Interstitial macrophages are differentiated from alveolar macrophages by their localization, regulating immune reactions and participating in the inflammation process. During ARDS, both alveolar macrophages and interstitial macrophages are activated, which could then release excessive proinflammatory cytokines and result in lung tissue injury [ 39 , 40 ]. ROS is a very important factor driving inflammatory response, which performs an integral role in the development of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial macrophages are differentiated from alveolar macrophages by their localization, regulating immune reactions and participating in the inflammation process. During ARDS, both alveolar macrophages and interstitial macrophages are activated, which could then release excessive proinflammatory cytokines and result in lung tissue injury [ 39 , 40 ]. ROS is a very important factor driving inflammatory response, which performs an integral role in the development of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…and Sophora moocrorftinan with antitumour, anti-inflammatory and antiviral activities. 111 Studies have shown 112 that mice with LPS-induced ALI exhibit hyperaemia in the large alveolar wall, thickening of the lung interstitium, inflammatory cell infiltration, and increased expression of inflammatory factors (HMGB1, TNF-α, IL-6 and IL-1β) in lung tissue and serum. The expression of autophagy-related proteins was increased, autophagy flux was increased, and TLR4, MYD88, P65 and P-mTOR protein levels in lung tissues were also increased.…”
Section: Sophoridinementioning
confidence: 99%
“…Thus, it can be speculated that macrophage autophagy impedes the production of inflammatory mediators and alleviates inflammatory responses in asthma. Activation of autophagy macrophage by sophoridine, a natural compound, alleviates LPS-mediated inflammation and acute lung injury by suppressing the TLR4/NF- κ B and mTOR signaling pathways [ 58 ]. Further investigation of the regulation of macrophage autophagy in asthmatic inflammation could provide a promising therapeutic strategy for this disease.…”
Section: Effects Of Modulating Macrophage Autophagy On Asthmamentioning
confidence: 99%